Chyle Leak Following Neck Dissection: Could Radiotherapy Be Considered a Management Option?. Issue 2 (March 2016) - De Felice, Francesca; Musio, Daniela; Musella, Angela; Tombolini, Mario; Tombolini, Vincenzo
Abstract : Abstract: Chyle leak after neck dissection is a relatively rare complication in head and neck cancer scenario. This review summarizes the basic knowledge of chyle leak underlying the potential benefit induced by low-dose radiation therapy and may serve as basis for future studies, necessary to optimize chyle leak management in head and neck cancer patients.